Platelet storage and functional integrity - Vit, Gianmatteo; Klüter, Harald; Wuchter, Patrick (Journal of laboratory medicine, 2020)
Platelet transfusion is a topic of common interest for many specialists involved in patient care, from laboratory staff to clinical physicians. Various aspects make this type of transfusion different from those of other blood components. In this review, the challenges in platelet transfusion practice that are relevant for laboratory colleagues will be discussed, highlighting how the biochemical and structural characteristics of these blood elements directly affect their function and consequently the clinical outcome. More than 1,300 platelet concentrates are transfused in Germany every day, and several types are offered by their respective manufacturers. We describe the technological advances in platelet concentrate production, with a focus on how the storage conditions of platelets can be improved. Laboratory quality assessment procedures for a safe transfusion are discussed in detail. For this purpose, we will refer to the Hemotherapy Directives ( Richtlinie Hämotherapie ) of the German Medical Association.